PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK TERHADAP SEMANGAT BELAJAR PEMBELAJARAN PENDIDIKAN PANCASILA BAGI SISWA KELAS 4 SDIT INSAN MULIA SEMARANG - Nova Laurina Ramadhani; Shafira Okta Chairunisa; Susilo Tri Widodo; Umroh Nurus Shobichah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was conducted in class 4 of SDIT Insan Mulia Semarang in the first semester of 2023 with 20 students. The purpose of this research was to find out information regarding the use of the talking stick learning model, especially in Pancasila Education learning, on the enthusiasm for learning of class 4 students at SDIT Insan Mulia Semarang. With research actions, namely learning activities without using the talking stick method and learning activities using the talking stick method. The research method used is a qualitative method in the form of observation. The research was carried out by observing grade 4 teachers and grade 4 students at SDIT Insan Mulia Semarang. The research results obtained show that class 4 students are more contributing and enthusiastic in learning Pancasila education using the talking stick model.